Non-Fiction from a Historical Perspective: Situation of Lithuanian Statemen Amid Tragic Events of 1940–1941 - Юрате Ландсберґіте-Бехер (Pitannâ Lìteraturoznavstva, 2024)
Non-fiction literature has become the crucial historical drama of the present, with its power to change the fate of the state and its interpretations. The line of statehood defence in the context of history or the so-called Mannerheim line is crucial in texts accessing only destroyed documentary sources left from decades of occupation. It is characteristic of the current era, in which real wars of history develop, and fiction causes the need for non-fiction looking for explanations, facts and illuminating shadowed destruction of the State and still dark turns of Lithuania’s historical path. Several episodes of non-fiction electrify society even today. There are unresolved questions where non-fiction is invaluable to changing the pro-Soviet historical narrative. The first question is the meeting of the last Government and the loss of Independence on June 15, 1940. Most Lithuanians believe it was President Antanas Smetona’s guilt (1874–1944), though he voted against the Soviets’ ultimatum and realised where things were leading. The question about the President’s guilt for leaving Lithuania and his mysterious death in an “accidental” fire in the USA is still influential in contemporary Lithuania but seems to have failed for genuine historical research. The following unresolved question is about the June Uprising against the Soviets during the invasion of the German army and the role of Colonel Kazys Škirpa in collaboration with Nazis or being their enemy. Historian and journalist Vidmantas Valiušaitis is engaged in the historical decoding of the Lithuanian Statehood path and building its own Mannerheim line, actually for predicting the fate of Ukraine and a new war with the Imperial ambitions of Russia in Europe.